Immigration to Korea: A Fiscal Boon or Burden? - Hur, Jinwook (KDI Journal of Economic Polilcy, 2020)
This paper intends to examine the extent of the fiscal contribution of immigrants to Korea. According to this analysis, the aim is to derive implications pertaining to the direction of Korea’s immigration policy as a response to fiscal problems caused by population aging. For this purpose, a macroeconomic model is designed to measure the lifetime net fiscal contribution of immigrants in Korea by visa type, age, and other characteristics. According to this analysis, the sum of the lifetime fiscal contribution for all immigrants in Korea is negative. This implies that immigration policy reforms that increase the inflow size while maintaining the current structure of the foreign population characteristics can rather worsen Korea’s fiscal problems. This finding suggests that immigration policy reform may exacerbate Korea’s fiscal soundness if it simply targets the maintenance of the numerical balance of the demographic structure.
Keywords: Immigration; Fiscal Sustainability; Population Aging